The global cardiovascular magnetic resonance registry (GCMR) of the society for cardiovascular magnetic resonance (SCMR): its goals, rationale, data infrastructure, and current developments. Issue 1 (December 2017) - Kwong, Raymond; Petersen, Steffen; Schulz-Menger, Jeanette; Arai, Andrew; Bingham, Scott; Chen, Yucheng; Choi, Yuna; Cury, Ricardo; Ferreira, Vanessa; Flamm, Scott; Steel, Kevin; Bandettini, W.; et al.
Abstract Background With multifaceted imaging capabilities, cardiovascular magnetic resonance (CMR) is playing a progressively increasing role in the management of various cardiac conditions. A global registry that harmonizes data from international centers, with participation policies that aim to be open and inclusive of all CMR programs, can support future evidence-based growth in CMR. Methods The Global CMR Registry (GCMR) was established in 2013 under the auspices of the Society for Cardiovascular Magnetic Resonance (SCMR). The GCMR team has developed a web-based data infrastructure, data use policy and participation agreement, data-harmonizing methods, and site-training tools based on results from an international survey of CMR programs. Results At present, 17 CMR programs have established a legal agreement to participate in GCMR, amongst them 10 have contributed CMR data, totaling 62, 456 studies. There is currently a predominance of CMR centers with more than 10 years of experience (65%), and the majority are located in the United States (63%). The most common clinical indications for CMR have included assessment of cardiomyopathy (21%), myocardial viability (16%), stress CMR perfusion for chest pain syndromes (16%), and evaluation of etiology of arrhythmias or planning of electrophysiological studies (15%) with assessment of cardiomyopathy representing the most rapidly growing indication in the past decade. Most CMR studies involved the use of gadolinium-based contrast media (95%). Conclusions We present the goals, mission and vision, infrastructure, preliminary results, and challenges of the GCMR. Trial registration Identification number on ClinicalTrials.gov:NCT02806193 . Registered 17 June 2016.